Board Social Capital and Corporate Social Responsibility Reporting: A panel Study from Listed Kenyan Firms - Yego, Jacob K.; Korir, Michael (African Journal of Education,Science and Technology (AJEST), 2022)
The primary objective of this study is to examine the impact of board relations on CSR reporting as a critical component of board social capital. This research also takes into account board size, firm size, firm age, and firm profitability as controls. The sample consists of Kenyan listed firms on the Nairobi Securities Exchange from 2009 to 2020. A panel data model with fixed effect regression is used. Based on a resource dependence perspective, show a significant positive relationship between board relations and the level of CSR reporting. These findings contribute to academic discourse about the social capital of board members. The authors, in particular, emphasize the significance of board relationships and their implications for decision making regarding CSR reporting. This evidence may be useful to firms when forming boards of directors, as well as regulators and professional organizations when reassessing legislation and guidelines